THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDES OF PARTICULAR WOMEN REGARDING COLOSTRUM BREAST MILK IN THE BATARAGURU HEALTH CENTER, WOLIO DISTRICT, BAUBAU CITY - Pratiwi, Cindy; Indang, Wa Ode; Zulaeha, Sitti (Institut Kesehatan dan Teknologi Buton Raya, 2024)
Colostrum is the milk produced on the first day arrival the third day after baby was born colostrum is the first milk that is produced, produced by the mother breast in the form of a yellowish liquid or clear syrup that contains higher protein and less fat and in ripe milk. Tp find out the relationship between knowledge and giving postpartum mothers about colostrum ASI at the Bataraguru City Health Center Baubau Year 2023.This study used a research Analytical survey design, the subject were postpartum women with knowledge and attitude, the data collection methods were primary and secondary data, data analysis consisted of data reduction, presentation and drawing conclusions.Chi Square test analysis P Value obtained (0,04) a (0,05), then H1 is accepted where there is relationship between knowledge and attituted of postpartum mothers towards colostrum breastfeeding at the Bataraguru Health Center, Wolio District, 2023.The management of early initiation of breastfeeding as initial act of giving colostrum to health services should be done better.